The entrepreneurial experience of a district figure of the Vyatka governorate during the late 19th – early 20th centuries (using I.N. Kibardin as an example) - D.V. Kondrashin (Ученые записки Казанского университета: Серия Гуманитарные науки)
I.N. Kibardin, the representative of the Vyatka region district intelligentsia, achieved significant success in the entrepreneurial activity during the establishment of capitalism in the Russian province. His numerous commercial projects – library, printing office, bookshop, and newspaper publishing – in Yelabuga, the city of a district status in the Viatka governorate – were interrelated. Each separate initiative contributed to the capitalization of his printing business. In this industry, I.N. Kibardin was a nontrivial example: the simple typographical production of the Vyatka province became a company capable of producing nationwide publications that took a leading position in the governorate. The experience of I.N. Kibardin is of interest for studying capitalism formation at the local level of the Russian province in the late 19th – early 20th centuries. The maximum development of the market opportunities of the Russian hinterlands by the entrepreneur was achieved under the state policy of restrictions and emerging demands of the society for the product he offered. He proved the efficiency of the mechanisms of bourgeois development at the local level. From the point of view of historical personology, the unique path of the “little man” who advanced by himself to prominent positions in the business community of the region is of particular interest. The relevance of the research lies in the anthropological approach to the study of the history of Russian entrepreneurial activity during the late 19th – early 20th centuries, in focusing on the background historical figure who was devoid of the halo of uniqueness and elitism.